2021
DOI: 10.18203/2349-2902.isj20212792
|View full text |Cite
|
Sign up to set email alerts
|

Study of the efficacy of trauma and injury severity score to predict survival in patients of polytrauma

Abstract: Background: Trauma is one of the major cause of mortality and morbidity in both developed and developing countries. Polytrauma patients present particular challenges as profile of the patient varies with different types and severity of injuries. Prediction of survival in trauma patients is an essential requirement of trauma care. Trauma and injury severity score (TRISS) have been considered as a standard of the quality of trauma care. Study was carried out to evaluate the performance of TRISS in predicting sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Regarding mortality, 16 patients (32%) died. This result is in contrast to Singh, A et al who found mortality only 16%cases [9]. Also, Attia, et al found mortality in 25% [7].…”
Section: Discussionmentioning
confidence: 60%
“…Regarding mortality, 16 patients (32%) died. This result is in contrast to Singh, A et al who found mortality only 16%cases [9]. Also, Attia, et al found mortality in 25% [7].…”
Section: Discussionmentioning
confidence: 60%
“…This is similar to local and international studies. [ 9 , 11 , 14 , 15 ] Young people are active in commercial activities and their involvement leads to a significant loss of man-hours and subsequent impact on economic activities.…”
Section: Discussionmentioning
confidence: 99%